Feminist lenses for the renewal of Marxism: exchange of views - Marinho, Silvana (Critical Proposals in Social Work, 2023)
This article seeks to offer some theoretical-political bases for a necessary discussion: that Marxian categories have a history and a dynamism, and, because they are more complex in the present, they require to be saturated with new historical and social determinations. In this effort, the Marxian ontology of social being is the analytical ground for this paper, which walks through feminist contributions that renew the reading of the relations of oppression-exploitation of class, race, and gender in the present time. This reflection intends, besides pointing out the renewal of Marxism by feminisms, to widen the lenses that allow translating the structural elements of the historical and current social precariousness of Brazilian women, in face of the de-democratization process imposed by the neoliberal and neoconservative project.